Multiomics joint analysis reveals the potential mechanism of differences in the taproot thickening between cultivated ginseng and mountain-cultivated ginseng - Meng Zhang; Yingxin Sun; Yiming Lan; Lin Cheng; Zeliang Lv; Mei Han; Limin Yang (BMC Genomics)
Abstract Panax ginseng is an important medicinal plant in China and is classified into two types: cultivated ginseng (CFCG) and mountain-cultivated ginseng (MCG). The two types of genetic varieties are the same, but the growth environments and management practices are different, resulting in substantial differences in their taproot morphology. Currently, there is a paucity of research on the internal mechanisms that regulate the phenotypic differences between cultivated ginseng and mountain-cultivated ginseng. In this study, we explored the potential mechanisms underlying their phenotypic differences using transcriptomic and metabolomic techniques. The results indicate that the taproot thickening of CFCG was significantly greater than that of MCG. Compared with MCG-4, MCG-10, and MCG-18, the diameters of the taproots of CFCG-4 increased by 158.96, 81.57, and 43.21%, respectively. Additionally, the contents of sucrose and starch in the taproot, as well as TRA and DHZR, were markedly elevated. Transcriptome analysis revealed that compared with MCG of different age groups, genes associated with starch and sucrose metabolism pathways (PgSUS1, PgSPS1, PgSPS3, and PgglgC1) were significantly upregulated in CFCG-4, whereas genes involved in the phenylpropanoid biosynthesis pathway (PgPER3, PgPER51, and PgPER12) were significantly downregulated in CFCG-4. This imbalance in the metabolic pathways suggests that these genes play crucial roles in ginseng taproot thickening. PgbHLH130 and PgARF18 may be key regulators of transcriptional changes in these pathways. These findings elucidate the molecular mechanisms governing ginseng taproot thickening, and have important implications for enhancing the overall quality and value of ginseng.